Best practice principles for communicating safety messages in national parks. (March 2019) - Saunders, Rob; Weiler, Betty; Scherrer, Pascal; Zeppel, Heather
Abstract: Effective communication of safety information for visitors to national parks and other protected areas is essential, particularly where the potential consequences of incidents are severe. Signs are often the primary communication tool for safety messages in national parks. Compliance-based approaches to safety signs using standards drawn from occupational safety are common, though empirical research into the effectiveness of safety signs in national parks and protected areas generally remains limited. To encourage a more pro-active approach to visitor safety, this paper offers an alternative by proposing and field-testing best practice principles (BPPs) for safety signs in parks. It first presents a literature review of safety sign research that, together with consideration of the current policy and practice of leading protected area management agencies, underpinned the development of three sets of BPPs for communicating safety messages. The set of BPPs that focused on safety signs in national parks were then field-tested in two Australian states. The results point to the theoretical as well as the practical value of best practice principles. In particular, they help reveal why and how particular signs are effective at communicating safety messages. From a management perspective, the BPPs offer a holistic yet contextually-adaptable approach to benchmarking and evaluation. The three sets of BPPs also draw attention to the importance of both a coordinated interpretation and communication approach and an overarching risk management framework in which the use of safety signage is embedded. Management implications: ● The paper presents best practice principles for safety signage and communication for managing visitor risk in protected areas. In addition the following aspects should be considered to enhance the effectiveness of warning concepts: ● Insights into the target audience including the respective awareness of risks and cultural differences in the various countries of origin. ● Familiarity with and perception of possible risks within different visitor segments. ● Familiarity with the presented communication means (illustrations, language, colors). ● Information prior to the stay to avoid inappropriate expectations and increase the awareness of possible risks.